PENGARUH TINGKAT KONSUMSI KAFEIN PENGARUH TINGKAT KONSUMSI KAFEIN BERLEBIHAN TERHADAP FOKUS BELAJAR MAHASISWA KEDOKTERAN TAHUN KE-3 UNIVERSITAS CIPUTRA : PENGARUH TINGKAT KONSUMSI KAFEIN BERLEBIHAN TERHADAP FOKUS BELAJAR MAHASISWA KEDOKTERAN TAHUN KE-3 UNIVERSITAS CIPUTRA - Melisa Grace Giovani Giovani (Jurnal Medika Hutama, 2026)
Abstract Third-year medical students face intensive academic demands, often relying on caffeine consumption to sustain study hours and enhance concentration. As an adenosine receptor antagonist, caffeine is known to reduce drowsiness and increase alertness; however, excessive intake may lead to sleep disturbances and diminished study focus quality. This study aims to identify caffeine consumption patterns among third-year medical students and analyze their relationship with study focus quality. A quantitative correlational approach was employed using a questionnaire covering demographic data, sleep habits, formal study hours, caffeine consumption patterns, consumption purposes, dependency levels, and study focus indicators. The sample consisted of active students consuming caffeine at least three times per week. Results showed that the majority of respondents were female, aged 19–21 years, with an average sleep duration of 5–6 hours per night and formal study hours of 9–12 hours per day. Coffee was the primary source of caffeine, with an average intake of 1–2 cups per day, while energy drinks and caffeine tablets were consumed by a small proportion of respondents. The main purposes of consumption were to reduce drowsiness and improve focus, with dependency levels ranging from low to moderate. Study focus indicators were predominantly at moderate scores (2–3), with variations influenced by sleep patterns and caffeine consumption. These findings highlight that excessive caffeine intake does not fully enhance study focus quality, underscoring the need for education on safe caffeine consumption limits and non-pharmacological strategies for academic stress management. Keywords: caffeine; medical students; sleep; study focus